2019
DOI: 10.1136/bmjspcare-2019-001824
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety incidents in advance care planning for serious illness: a mixed-methods analysis

Abstract: ObjectivesAdvance care planning (ACP) is essential for patient-centred care in the last phase of life. There is little evidence available on the safety of ACP. This study characterises and explores patient safety incidents arising from ACP processes in the last phase of life.MethodsThe National Reporting and Learning System collates patient safety incident reports across England and Wales. We performed a keyword search and manual review to identify relevant reports, April 2005–December 2015. Mixed-methods, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…14 15 However, most of the evidence describing the nature of patient-reported safety incidents has originated from the hospital setting, 16 with primary care considered an emerging research area. [17][18][19][20][21][22][23][24][25][26] A small number of studies have described the frequency of patient-reported safety incidents or errors, and harm in primary…”
Section: Introductionmentioning
confidence: 99%
“…14 15 However, most of the evidence describing the nature of patient-reported safety incidents has originated from the hospital setting, 16 with primary care considered an emerging research area. [17][18][19][20][21][22][23][24][25][26] A small number of studies have described the frequency of patient-reported safety incidents or errors, and harm in primary…”
Section: Introductionmentioning
confidence: 99%
“…We have already applied this mid-range programme theory to our later analysis of incidents arising from advance care planning. 31 This identified structure-based solutions to ensure patients receive timely and robust advance care planning would not be enough; in 37% (26 of 70) of advance care planning incidents, the plan was not followed due to person-level issues such as poor higher-level meta-cognitive skills or emotional intelligence often in the context of lack of confidence or experience.…”
Section: Discussionmentioning
confidence: 99%
“…The PatIent SAfety (PISA) Research Group at Cardiff University has led an extensive characterisation of patient safety incidents reported by healthcare professionals from primary and secondary care settings. This includes studies to identify priority areas for patient safety across the health and social care continuum, including unsafe discharge from secondary to primary care settings [ 18 ], incidents experienced by children in primary care [ 19 ], older adults [ 20 ], patients receiving palliative care [ 21 ], advanced care planning [ 22 ] and adults receiving opiate replacement therapy [ 23 ]. The PISA classification system has also previously been used to characterise the nature of patient-reported safety incidents in primary care settings from the UK and Australia, enabling the data to be used for service learning and improvement [ 24 ].…”
Section: Methodsmentioning
confidence: 99%